Ruminal Degradability and Bypass Nutrients of Alkaline or Steam-Treated Cassava Chip and Corn Grain - W. Srakaew; C. Wachirapakorn; A. Cherdthong; C. Wongnen (Tropical Animal Science Journal, 2021)
Modification of starches in high-energy feeds using various treatment methods led to the diverse effects on ruminal degradation and bypass protein and starch. Thus, the objectives of the present experiment were to investigate the effects of modification methods applied to high-starch energy feed sources on ruminal degradability and bypass nutrients determined using in situ and in vitro gas production techniques. This experiment was designed using a 2×4 factorial arrangement in a completely randomized design (CRD). The first factor was high-starch energy feed consisted of two levels, i.e., corn grain and cassava chips. The second factor was the treating method consisted of four levels, i.e., no treatment, steam treatment, NaOH treatment, and steam with NaOH treatment. Chemical composition, ruminal in situ disappearance, bypass of crude protein (CP) and non-fiber carbohydrate (NFC), and gas production characteristics were measured in pre-treated and post-treated samples. The results showed that significant interactions (p<0.01) between high-starch energy feed sources and treating methods were observed with respect to CP, ether extract (EE), and NFC, dry matter degradability (DMD), effective degradation (ED), and effective gas production (EP). Cassava chips had lower CP and EE but higher NFC, DMD, ED, and EP (p<0.01) compared with corn grain. Treating methods have no influence on CP and EE (p>0.05) in cassava chips and corn grain. DMD, ED, and EP of treated cassava chips were lower, while bypass CP and bypass NFC of treated cassava chips were higher than untreated cassava chips (p<0.05). On the contrary, treated corn grain led to higher DMD, ED, and EP, but lower bypass CP and bypass NFC than untreated corn grain did (p<0.01). DMD and gas production characteristics in cassava chips and corn grain showed significant correlations between in situ nylon bags and in vitro gas production techniques within each high-starch energy feed source. In conclusion, steam and NaOH treatments are two alternative methods that can modify the starches of high-starch energy feeds to alter ruminal degradation by decreasing solubility and degradability in cassava chips but increasing degradability in corn grain.